Experimental characterization of moisture transport in brick masonry with natural hydraulic lime mortar. (November 2021) - Ramirez, R.; Ghiassi, B.; Pineda, P.; Lourenço, P.B.
Abstract: This article presents an experimental study on the hygric performance of brick masonry with a special focus on the hydraulic characterization of the brick-mortar interface. The hygric behavior was studied at the level of the constituent materials as well as at the composite scale. An extruded fired-clay brick and two types of mortar –Portland cement mortar and natural hydraulic lime mortar– were chosen as target materials. The hygric properties were determined following prescribed experimental procedures. The experimental program included vacuum saturation tests, static gravimetric tests for adsorption/desorption isotherms, dry/wet cup tests, capillary absorption tests, and isothermal one-dimensional drying. The results allowed for a comprehensive identification of the main hygric features of the target materials. Fired-clay brick and lime mortar revealed low hygroscopicity and a strong capillary-active behavior with negligible hysteresis, whereas cement mortar showed activity in both hygroscopic and capillary ranges with a distinct moisture storage hysteresis. Different curing conditions led to dissimilar properties between the lime mortar prepared in molds and the same mortar cured in masonry bed joints. Water absorption in fired-clay bricks showed a marked anisotropic behavior, likely derived from the extrusion process. The existence of an imperfect hydraulic contact at the brick-mortar interface was demonstrated for water absorption. Conversely, the interfacial effect on drying kinetics was not evident. Highlights: Experimental study on moisture transport in brick masonry. Hygric characterization of masonry constituent materials. Hygric behavior of masonry composites studied by water absorption and drying tests. Dissimilar behavior between mortar cured in molds and mortar in masonry bed joints. Hydraulic resistance at the brick-mortar interface in multi-layered specimens.